Analysing the Influence of Carbon Prices on Users’ Energy Cost and the Positive Impact of Renewable Energy Sources - Daniele Groppi; Lorenzo Mario Pastore; Davide Astiaso Garcia; Livio de Santoli (Journal of Sustainable Development of Energy, Water and Environment Systems, 2025)

(untitled)
Decarbonisation is a difficult process and a core scepticism lies in the potentially higher cost of energy due, for instance, to the Emission Trading System. It is possible to analyse the energy transition process and provide guidance for policy actions thanks to integrated planning tools. This research explores the impact of carbon prices on the optimal design of the Italian energy system in order to understand their influence on the uptake of renewable energy sources as well as on consumers’ energy cost. The research employs the H2RES software under different carbon pricing scenarios and understand its impact on the optimal energy mix, cost of electricity and hydrogen. The outcomes show how different carbon price trends lead to different energy costs until 90% renewable penetration, point at which the energy mix is mostly detached from carbon pricing mechanisms and energy costs become stable and independent from external price signals.